2017
DOI: 10.3945/ajcn.117.156232
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of habitual coffee consumption and glycemic changes in response to weight-loss diet intervention: the Preventing Overweight Using Novel Dietary Strategies (POUNDS LOST) trial

Abstract: Background: Coffee consumption has been associated with glucose metabolism and risk of type 2 diabetes. Objective: We examined whether the genetic variation determining habitual coffee consumption affected glycemic changes in response to weight-loss dietary intervention. Design: A genetic risk score (GRS) was calculated based on 8 habitual coffee consumption-associated single nucleotide polymorphisms. We used general linear models to test changes in glycemic traits in groups randomly assigned to high-and low-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
5
2
Order By: Relevance
“…The effect of coffee consumption on plasma glucose is controversial [29]. The negative effects of coffee intake on insulin level, resistance, and blood glucose level seem to be genetically determined [30]. The present study showed no correlation between coffee intake and the glycated hemoglobin.…”
Section: Discussioncontrasting
confidence: 64%
“…The effect of coffee consumption on plasma glucose is controversial [29]. The negative effects of coffee intake on insulin level, resistance, and blood glucose level seem to be genetically determined [30]. The present study showed no correlation between coffee intake and the glycated hemoglobin.…”
Section: Discussioncontrasting
confidence: 64%
“…The effects of coffee consumption on plasma glucose is controversial [29]. The negative effects of coffee intake on insulin level, resistance, and blood glucose level seem to be genetically determined [30] The present study showed no correlation between coffee intake and the glycated hemoglobin. Yarmolinsky et al [31] observed the protective effects of coffee consumption on diabetes mainly through the effect on postprandial blood glucose.…”
Section: Discussioncontrasting
confidence: 68%
“…Besides caffeine, brewed coffee contains several bioactive compounds including polyphenols and diterpene alcohols such as cafestol and kahweol, which are associated with lower incidences of metabolic syndrome and CVD risk factors including high blood pressure, plasma cholesterol, and homocysteine (Hcy) [ 15 , 17 , 24 , 25 ]. Epidemiological studies indicate that higher coffee consumption reduced the genetic associations with body mass index (BMI) and obesity risk and type 2 diabetes [ 26 , 27 , 28 ]. Gene–diet interaction analysis in three US prospective studies indicated that the higher consumption of coffee was associated with reduced obesity risk among individuals who were genetically predisposed to obesity as measured by 77 BMI-associated single nucleotide polymorphisms (SNPs) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies indicate that higher coffee consumption reduced the genetic associations with body mass index (BMI) and obesity risk and type 2 diabetes [ 26 , 27 , 28 ]. Gene–diet interaction analysis in three US prospective studies indicated that the higher consumption of coffee was associated with reduced obesity risk among individuals who were genetically predisposed to obesity as measured by 77 BMI-associated single nucleotide polymorphisms (SNPs) [ 26 ]. Similarly, in a weight loss intervention study, the genetic risk factors consisting of eight habitual coffee consumption-associated SNPs related to coffee and glucose metabolism was reduced by habitual coffee consumption [ 27 ].…”
Section: Introductionmentioning
confidence: 99%